An initiative for a morphologic‐genetic catalog of relict charcoal hearths from Central Europe. Issue 6 (7th June 2020) - Hirsch, Florian; Schneider, Anna; Bonhage, Alexander; Raab, Alexandra; Drohan, Patrick J.; Raab, Thomas
Abstract: The increasing availability of high‐resolution topographic data, coupled with image analysis and machine learning techniques, is rapidly changing the way archaeological sites are digitally identified and mapped. We present a catalog of common forms of relict charcoal hearths (RCHs) in Central Europe to improve the evaluation of morphologic and genetic features in future mapping approaches. RCHs are important historical landscape features created from the production of charcoal. RCHs are noted in Central Europe from the Medieval Period, but also are widespread near (pre‐)industrial mining centers. Different forms of charcoal hearths were created by workers known as colliers, and their hearth building techniques may have differed on a regional scale. Our catalog is based on a morphologic–genetic grouping of RCHs. Due to topographic effects, reuse of production sites, or local techniques, this catalog is nonexhaustive, but most RCHs in Central Europe can be grouped into one of seven types.